The construction of teaching learning: hearing licensing in supervised curriculum internship - Pagliarin, Lidiane Limana Puiati (2019)
The aim of the research was to understand how teaching learning occurs in pedagogy students, highlighting the processes and formative contexts (ILLERIS, 2013; LAVE, 2013) that made learning possible. The sources of information were narratives constructed in focus groups by academics in their first supervised curricular internship in basic education. In summary, the learning emphasized was the knowledge of the subjects with which they worked and the understanding of teaching as a profession. The most cited learning contexts were university and school. In synthesis, there are several learning processes being (re) constructed, originating from both individual processes and also from interactions with other subjects.